Entrepreneurs’ social identity and the preference of causal and effectual behaviours in start-up processes - Gry Agnete Alsos; Tommy Høyvarde Clausen; Ulla Hytti; Sølvi Solvoll (Taylor & Francis, 2022)
This paper examines how the social identity of an entrepreneur influences his or her behaviour when engaged in new venture formation. Building on the typology of entrepreneurial identities developed by Fauchart and Gruber, this study examines the relationship between the social identity of the entrepreneur and subsequent entrepreneurial behaviour using a mixed-method approach. Based on interviews with entrepreneurs in six start-ups within the tourism sector and on previous literature, three hypotheses were developed regarding the relationship between entrepreneurial identity and entrepreneurial behaviour (causation, effectuation). Subsequently, the hypotheses were tested using a survey among a sample of entrepreneurs who registered a new firm in 2013. The study finds that the entrepreneurial identity influences whether the individual predominantly engages in effectual or causal behaviour. Hence, the study contributes by focusing on entrepreneurial identity as an important factor shaping the behaviours of entrepreneurs. In addition, we add to the understanding of entrepreneurs as a heterogeneous group. Entrepreneurs vary in terms of their identity, and this variation has consequences for their entrepreneurial behaviour. Finally, by adopting a mixed-method approach, this study benefits from and contributes to the interaction of qualitative and quantitative data in entrepreneurship research.